Bryant & May : the lonely hour - Fowler, Christopher (Fowler, Christopher. Bryant & May mysteries., 2019)
"When a man is found hanging upside down inside a willow tree on Hampstead Heath, surrounded by a baffling assortment of occult objects, the Peculiar Crimes Unit is called in to investigate. Was this a botched Satanic ritual pulled off by bored teenagers, a gang initiation, or the work of a mastermind with grander intentions? Bryant and May set off for answers and soon discover that London is a city steeped in blood and magic. When another body is pulled from the river in the early morning light, it becomes clear that a killer lurks in the night. To catch him, the PCU switches to graveyard shifts, but the team still comes up short. As they explore a night city where the normal rules do not apply, they're drawn deeper into a case that involves murder, arson, kidnapping, blackmail, loneliness, and bats. May takes a technological approach, while Bryant goes in search of academics and misfits for help, for this is becoming an investigation that reveals impossibilities at every turn. How do you stop a killer who appears not to exist? Luckily, impossibilities are what the Peculiar Crimes Unit does best"--